Bosnia and Herzegovina : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) was prepared on the basis of the findings of a World Bank mission to Bosnia and Herzegovina in 2001, and reflects developments through early 2002. The CFAA was a constituent element of the Public Expenditure and Institutional Review (PEIR) published in June 2002 on the basis of work carried out in 2001-2002, and the key findings of the CFAA on the public expenditure policy and institutional framework form a significant part of the PEIR section dealing with financial management in the government sector. While some of the diagnosis presented in this CFAA may have been overtaken by events since early 2002, most of its recommendations remain valid and the report provides a sound analytical framework for ongoing reforms in the field of public expenditure management. The country is in transition not only to a market and a post-war economy, but also to a peculiar (and still fragile) conception of statehood. Public administration in BiH combines pre-war, wartime and post-war institutions, often exercising overlapping administrative authority. The administrative organs operating within a complex governmental structure, the international strategy focus is on building the institutional base of BiH's democracy and fiscal management, using international influence to protect key institutions during their vulnerable early phase, and bring them to a point where they can sustain themselves after international support is withdrawn. At the same time, the way to Europe being the creation of a single free economic space in BIH, harmonization and creation of common institutions are crucial. Statehood needs to be reinforced and specific areas need to be strengthened in the two Entities in view of the requirements for EU accession. The CFAA recommends support of the shift of key institutions and processes from the Entities to the State as advocated by the IC. Such a shift would empower State institutions with stable and predictable budgetary resources and ensure harmonized fiscal management and oversight. At the same time, to mitigate concerns about over-centralization, effective governance should be promoted at the cantonal and municipal levels, where financial accountability is also weak.